Interaction of cyclic and linear Labaditin peptides with anionic and zwitterionic micelles - Barbosa, S. C.; Cilli, E. M. [UNESP]; Dias, L. G.; Fuzo, C. A.; Degreve, L.; Stabeli, R. G.; Itri, R.; Ciancaglini, P. (Elsevier B.V., 2015)
Conformational changes of the cyclic (Lo) peptide Labaditin (VWTVWGTIAG) and its linear analogue (L-1) promoted by presence of anionic sodium dodecyl sulfate (SDS) and zwitterionic L-alpha-Lysophosphatidylcholine (LPC) micelles were investigated. Results from lambda(max) blue-shift of tryptophan fluorescence emission combined with Stern-Volmer constants values and molecular dynamics (MD) simulations indicated that L-1 interacts with SDS micelles to a higher extent than does Lo. Further, the MD simulation demonstrated that both Lo and L-1 interact similarly with LPC micelles, being preferentially located at the micelle/water interface. The peptide-micelle interaction elicits conformational changes in the peptides. Lo undergoes limited modifications and presents unordered structure in both LPC and SDS micelles. On the other hand, L-1 displays a random-coil structure in aqueous medium, pH 7.0, and it acquires a beta-structure upon interaction with SDS and LPC, albeit with structural differences in each medium. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Labaditin; Cyclic peptide; Circular dichroism; Fluorescence; Molecular dynamic